IMPLIKASI PENGHAPUSAN DESA TERHADAP KESEJAHTERAAN MASYARAKAT DESA - Dani, Akhmad; Johansyah, Johansyah (Faculty of Law, University of Palembang, 2022)
The discourse on the abolition of the village has given birth to legal implications that are inconsistent with the values ​​of certainty, justice, and usefulness that will be achieved in the purpose of structuring the village so that it has an impact on the continuation of the welfare of the village community. This is reflected in the management of village income and Village-Owned Enterprises which result in a legal vacuum after the abolition of the village so that the achievement of village community welfare will be hampered as mandated by the constitution in the Preamble to the 1945 Constitution of the Republic of Indonesia. Implications for the abolition of villages are included in village planning as regulated in statutory regulations Number 6 of 2014 concerning Villages. There is a clause on the purpose of village structuring which becomes a legal rule that should be carried out (das sollen) but there is a discrepancy when the legal rule is faced with the abolition of the village (das sein) because the abolition of the village has eliminated all provisions for the purpose of village structuring, so that villages that experience abolition in ultimately not oriented towards the purpose of structuring the village. On the other hand, the subjective legal reasons for the elimination of villages have reduced the role of the village in the elimination of villages by policies caused by the central government, which should involve local and village governments.